A multistate investigation of a solar dryer coupled with photovoltaic thermal collector and evacuated tube collector. (15th March 2020) - Daghigh, Roonak; Shahidian, Roonak; Oramipoor, Hooman
Highlights: A photovoltaic thermal – evacuated tube dryer with and without set points examined. Two new model to predict the drying process of Tarkhineh was presented. The life-cycle cost analysis (LCCA) of Tarkhineh was performed. The payback period of the PV/T dryer and ET solar dryer were 2.3 and 2.5 years. Abstract: In this study, an indirect solar dryer was designed and manufactured using a Photovoltaic Thermal (PV/T) collector and Evacuated Tube (ET) collector. The main objectives of this system were to supply the thermal load of the indirect solar dryer, to find the best model for the drying process, to present a new model to predict the drying process of Tarkhineh (the drying material) and to perform its life-cycle cost analysis (LCCA). The manufactured system was tested under the weather conditions of Sanandaj city, Iran and was compared with open sun drying. When the auxiliary heater was not used, the new model 1 was the best model to describe the drying of Tarkhineh in the open sun mode and the new model 2 was the best model to describe the drying of Tarkhineh in the solar dryer designed and manufactured in this study. The new models 1 and 2 were found to be the best models for describing the drying process of Tarkhineh at set point temperatures 55 °C and 45 °C, supplied by the auxiliary heater, respectively. The payback period of the PV/T solar dryer and ET solar dryer, assuming 300 sunny days/year, were 2.3 and 2.5 years, respectively.